Implantable cardioverter defibrillator for primary prevention in patients with non-ischemic cardiomyopathy in the era of novel therapeutic agents- meta-analysis - Kolben, Yotam; Hirsh Raccah, Bruria; Koev, Ivelin; Luria, David; Amir, Offer; Biton, Yitschak (Frontiers in Cardiovascular Medicine, 2023)
Background Evidence regarding the mortality benefit of implantable cardioverter defibrillator (ICD) non-ischemic dilated cardiomyopathy (NIDCM) is inconsistent. The most recent randomized study, the DANISH trial, did not find improved outcomes with ICD. However, based on previous studies and meta-analyses, current guidelines still highly recommend ICD implantation in NIDCM patients. The introduction of novel medications for heart failure improved the clinical outcome dramatically. We aimed in this study to evaluate the effect of Angiotensin Receptor-Neprilysin Inhibitors (ARNi) and sodium-glucose transport protein 2 inhibitors (SGLT2i) on the mortality benefit of ICD in NIDCM. Methods We used a previous metanalysis algorithm and added an updated comprehensive literature search in PubMed for randomized control trials that examined the mortality benefit of ICD in NIDCM vs. optimal medical treatment. The primary outcome included death from any cause. We did a meta-regression analysis to search for a single independent factor affecting mortality. Using previous data, we evaluated the theoretical effect of ICD implementation on patients treated with SGLT2 inhibitors and ARNi. Results No new articles were added to the results of the previous meta-analysis. 2,622 patients with NIDCM from 5 cohort studies published between 2002 and 2016 were included in the analysis. 50% of them underwent ICD implantation for primary prevention of sudden cardiac death, and 50% did not. ICD was associated with a significantly decreased risk for death from any cause compared to control (OR = 0.79, 95%CI: 0.66–0.95, p = 0.01, I2 = 0%). The theoretical addition of ARNi and the SGLT2 inhibitor dapagliflozin did not change the significant mortality effect of ICD (OR = 0.82, 95%CI: 0.7–0.9, p = 0.001, I2 = 0%) and (OR = 0.82, 95%CI: 0.7–0.9, p = 0.001, I2 = 0%). A meta-regression revealed no association between death from any cause and left bundle branch block (LBBB), use of amiodarone, use of angiotensin-converting enzyme inhibitors (ACEi) or angiotensin receptor blockers, year initiated enrollment, and the year ended enrollment (R2 = 0.0). Conclusion In patients with NIDCM, the addition of ARNi and SGLT2i did not affect the mortality advantages of ICD for primary prevention. PROSPERO registry number https://www.crd.york.ac.uk/prospero/, identifier: CRD42023403210.